2017
DOI: 10.1038/s41598-017-00902-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 Deficiency Augments Inflammatory Response and Exacerbates Septic Heart and Renal Injury Induced by Lipopolysaccharide

Abstract: Septic acute kidney injury (AKI) and myocardial dysfunction are leading causes of mortality with no accepted method of therapy. In this study we demonstrate the role of growth differentiating factor 15 (GDF15) in septic AKI and myocardial dysfunction using a murine lipopolysaccharide (LPS)-induced sepsis model and an in vitro cell culture system. Data show that GDF15 deficiency augments inflammatory response and exacerbates renal and cardiac injury induced by LPS, while over-expression of GDF15 protects the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 35 publications
(54 reference statements)
3
60
0
1
Order By: Relevance
“…Recently, we also demonstrated that Liproxstatin-1 significantly accelerated the recovery of the hPSC-CMs functional properties such as beating frequency after the ETP treatment [41]. Interestingly, it was shown that treatment of the GDF15 knockout animals with lipopolysaccharide augmented the inflammatory response and aggravated septic heart and renal injury [64]. These recent findings support our hypothesis that GDF15 acts as a preventing agonist against DOX-induced heart injury.…”
Section: Is It Possible To Identify Common Factors Playing a Role In supporting
confidence: 82%
“…Recently, we also demonstrated that Liproxstatin-1 significantly accelerated the recovery of the hPSC-CMs functional properties such as beating frequency after the ETP treatment [41]. Interestingly, it was shown that treatment of the GDF15 knockout animals with lipopolysaccharide augmented the inflammatory response and aggravated septic heart and renal injury [64]. These recent findings support our hypothesis that GDF15 acts as a preventing agonist against DOX-induced heart injury.…”
Section: Is It Possible To Identify Common Factors Playing a Role In supporting
confidence: 82%
“…Zimmers et al [6] demonstrated induction of GDF-15 expression after kidney or lung injury in murine models and suggested that GDF-15 is an early mediator in organ injury. Abulizi et al [28] have determined that GDF-15 deficiency in a lipopolysaccharide-induced renal injury model aggravates renal damage. Other investigators demonstrated that genetic deletion of GDF-15 exacerbated injury in the renal interstitium and tubules in diabetic mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial dysfunction is a fatal complication of patients with sepsis [18]. Researches have found that 50% of patients with sepsis have systolic and diastolic dysfunction in left and right ventricular, possibly caused by endotoxin-induced myocardial injury [36] which has been confirmed both in animal and clinical observations [37]. In this study, we also confirm that CLP-induced sepsis caused serious myocardial damage characterized by significant reduction of left ventricular systolic and diastolic functions in mice, which closely mimicked the pathological features of myocardial infarction observed in clinical patients [38].…”
Section: Discussionmentioning
confidence: 86%